An investigation into the correlation between intraperitoneal teicoplanin concentrations and treatment outcomes in peritoneal dialysis-associated peritonitis - Wang, Lulu; Fan, Jiangqing; Chen, Xuejie; Lei, Wenpu; Jiang, Chunming; Liu, Hang; Yang, Yun; Shen, Jizhong (Frontiers in Pharmacology, 2024)
Peritoneal dialysis-associated peritonitis (PDAP) is a frequent complication of peritoneal dialysis. The guidelines from the International Society for Peritoneal Dialysis (ISPD) suggest administering teicoplanin through the peritoneal route to treat PDAP, but do not specify the ideal concentration for peritoneal dialysis effluent (PDE). Patients meeting the trial criteria for PDAP in our hospital between July 2022 and December 2023 were enrolled. Data on PDE white blood cell count, PDE neutrophil percentage, clinical symptoms, CRP, and PCT were gathered pre-and post-treatment. Incidences of ADR and case numbers during treatment were recorded. Subsequently, PDAP patients who use intraperitoneal teicoplanin could effectively control infection by considering the PDE teicoplanin concentration (> 15.138 mg/L) on day 5 after dosing.